Timing stability of millisecond pulsars and prospects for gravitational-wave detection - Verbiest, J.; Bailes, M.; Coles, W.; Hobbs, G.; van Straten, W.; Champion, D.; Jenet, F.; Manchester, R.; Bhat, N.; Sarkissian, J.; Yardley, D.; Burke-Spolaor, S.; et al. (Wiley-Blackwell Publishing Ltd., 2009)
The analysis of high-precision timing observations of an array of ~20 millisecond pulsars (aso-called 'timing array') may ultimately result in the detection of a stochastic gravitational wave background. The feasibility of such a detection and the required duration of this type of experiment are determined by the achievable rms of the timing residuals and the timing stability of the pulsars involved. We present results of the first long-term, high-precision timing campaign on a large sample of millisecond pulsars used in gravitational-wave detection projects. We show that the timing residuals of most pulsars in our sample do not contain significant low-frequency noise that could limit the use of these pulsars for decade-long gravitational-wave detection efforts. For our most precisely timed pulsars, intrinsic instabilities of the pulsars or the observing system are shown to contribute to timing irregularities on a 5-year time-scale below the 100 ns level. Based on those results, realistic sensitivity curves for planned and ongoing timing array efforts are determined. We conclude that prospects for detection of a gravitational-wave background through pulsar timing array efforts within 5 years to a decade are good.